AJARAN MORAL KGPAA MANGKUNAGARA IV BAGI MASYARAKAT JAWA PADA ERA GLOBAL - Edy Tri Sulistyo (Institut Seni Indonesia Surakarta, 2012)
This research aims at studying the understanding and response of the Javanese society to the moral teachings of KGPAA Mangkunegara IV in serat Wedhatama in this globalization era. The strategy used in this research is an embedded case study research. The data source made use in this research is the text in Serat Wedhatama. The data taken from literary studies is used to study the objective and genetic factors and the information obtained from cultural observers, lecturers of regional literature, members of Mangkunegaran palace is used to study the affective factor. The sampling technique used in this study was purposive sampling, while the data was collected through in-depth interviews and Focus Group Discussion (FGD), and then was analyzed using holistic critical analysis (Sutopo, 2006). The validity of the data was endorsed using the triangulation method. The results showed that the moral teachings of KGPAA Mangkunegara IV had a close relation to God Almighty, the wise method of social intercourse, nobleman in spirit, respect for other’s opinion and struggle for life. The moral teachings of KGPAA Mangkunegara IV summarized from Serat Wedhatama are as follows: (1) moral teachings in the forms of advices, guidance, persuasion, and messages; (2) warning; (3) prohibition; (4) criticism; (5) statements, and (6) teachings. The moral teaching offered is generally in the form of a suggestion through a metaphor. The suggestion given uses the method of esem mantri which means the smile of punggawa mantri and semu bupati which means the regent’s amusing face.Key words : moral teachings, Serat Wedhatama, Tembang Macapat, sanepa, esem mantra, punggawa mantra, and semu bupati